Formulation of Empirical Models for Solar Module by Optimisation of its Tilt-Angle Under Natural Conditions - Siow, Wee Siong (2001)
Malaysia is a tropical country with abundant sunshine all the year round. The use of solar energy as an alternative to the conventional should be developed urgently as the conventional fuels will be exhausted within this century. Information of global irradiance at any site of the country is essential for proper design and assessed for optimum solar energy conversion. The aim of this study is to find suitable empirical models to explain the incident global irradiance on solar modules for electrical conversion at a fixed optimum tilt-angle throughout the entire day and under the natural conditions. This research presents a comparative assessment of tilted insolation models using hourly measurements of constant global insolation on solar modules tilted at 0°, 15°, 30° and 45° oriented south in Universiti Putra Malaysia. The experimental research was carried out for six months by exposing the solar modules to natural environment where their environmental parameters such as global insolation, ambient temperature, solar cell temperature, wind speed, time, module-current and voltage at various load conditions were recorded. By using the recorded data, a variety of graphical and statistical analyses were performed in order to deduce the module's internal parameters and formulation of models. The analysis reviewed that the optimum tilt-angle was 150 due south as the solar module achieved the highest average global insolation and power production for the entire day during the test. Statistical regression analyses were also performed to formulate empirical models for showing the relationship between these environmental parameters. The formulated empirical models maybe able to predict the outcome of solar electricity production under various tih-angles and environmental parameters.